IMPLEMENTASI ACTIVITY BASED COSTING TERHADAP PERHITUNGAN BIAYA OPERASIONAL PADA UNIT LAYANAN RUMAH SAKIT X SURABAYA - Annisa Rahmawati; Achmad Daengs GS (Jurnal Riset Akuntansi, 2021)
Hospital is an institution that is in the realm of non-profit, where its main activities consist of medical activities, health services, and health education. During its development, hospital activities shifted to the business realm where apart from providing health services, the hospital also focused its activities as a business entity. This research was conducted at Hospital X, located in West Surabaya. In carrying out its economic activities, Hospital X charges its operational costs using a simple method. The research method used is a qualitative method. The research results show that the charging of operational costs with the Activity Based Costing method provides a more accurate and reasonable calculation of loading so that the results of these calculations can be used to compile financial reports with fair value and can be useful as a basis for calculations in order to determine service rates provided to the Hospital X.